Dielectric relaxation behavior of BaZrO3 ceramics at low temperature - Pulphol, Phieraya; Vittayakorn, Naratip; Vittayakorn, Wanwilai; Kolodiazhnyi, Taras (My University, 2020)
Dielectric behavior of nominally pure BaZrO3, Sc-doped BaZrO3 and Sc + Nb-co-doped BaZrO3 ceramics is reported in this paper. Several dielectric anomalies are detected in the pure and Sc-doped BaZrO3 in temperature interval of 2–700 K. The Arrhenius-type dielectric relaxation has activation energies ranging from ca. 10 meV–800 meV. Annealing in Ar atmosphere at 1200 °C alters the intensity of the dielectric loss peaks especially in the Sc-doped BaZrO3. In contrast, none of the dielectric relaxation anomalies were found in Sc + Nb-co-doped BaZrO3. It is proposed that at least some of the dielectric peaks originate from the proton dynamics which includes high temperature migration, intermediate-temperature rotation and low-temperature phonon-assisted proton tunneling.
Keywords: Barium zirconate; Dielectric anomalies; Phonon-assisted proton tunneling